Post-aural epidermoid cyst: a case of diagnostic detour - P., Oviya; Lakshmi S., Shabna; N., Nagendran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Epidermoid cysts are benign lesions arising from epidermal inclusions within the dermis. They are the most common cutaneous lesions occurring in the third and fourth decades of life. Although frequently seen in the head and neck region, post auricular localization with regional extension is rare. The most common presentation is a painless swelling; however, pain may occur in cases with complications such as cyst rupture, secondary inflammation, or infection. This case presented with recurrent history of painful swelling in the post aural region with extension into the supra aural and zygomatic area. After evaluating with USG and CT, incision and drainage was done. 2 weeks post procedure patient had reappearance of the swelling that prompted further evaluation. MRI showed a positive finding of T2 hyper intense homogenous lesion in post aural region with diffusion restriction and communication with the incision and drainage site. On surgical exploration cystic lesion in post aural region with a small track in the supra aural region seen. Complete removal with histopathological studies done showed the diagnosis of post aural epidermoid cyst. This case highlights the need of high suspicions index in cases with recurrence or atypical presentations. Radiological evaluation and histopathological examinations aids in concluding the diagnosis.